The Long Wait - Ayodele, Samuel O. (Evans Brothers (Nigeria Publishers) Limited, 2006)
Notwithstanding the strong pressure from Sola's immediate family to get him another wife in place of Tola who is yet bear him children, the love he has for his wife stands the test of time. However, the pressure continues until God intervenes and blesses them with a set of twins.
Keywords: Family; Juvenile Fiction